Positive and Negative Attitudes from the University Community on Prevention Measures during the 2020 Contingency - Fernández Poncela, Anna María (2021)
During 2020 the world faced many negative changes as reflected in speeches by international organizations, government and the media including citizen perception. The hypothesis of this study looks beyond the negative and also analyze positive attitudes during this period and with regards to how the study participants were impacted by the Covid emergency with reference also made to online education. The methodological design and data collection is based on the narrative accounts of individuals who participated in the study, all university students in Mexico City. Grounded theory was used for data analysis. Overall, two points of views prevailed – negative and positive perspectives. The importance of the former does not cancel out the latter. A recommendation was made for these students to embrace resilience so that they can better adapt to change. Given that the pandemic is still widespread, this experience must be replicated and intensified in order to continue to learn and grow as a result.